The Effect of Moringa Leaf Vegetables on Increasing Breast Milk For Breastfeeding Mothers 0-2 Years Old - Zakiyah Yasin (Universitas Muhammadiyah Jember, 2021)
A mother often has problems in exclusive breastfeeding, one of the main obstacles is the milk production that is not smooth. This will be a factor causing the low coverage of exclusive breastfeeding for newborns. Moringa leaves are plants that are rich in nutrients, namely antioxidants, vitamins, minerals, amino acids, anti-inflammatory and others. The nutritional content is so extraordinary, Moringa plants have the potential to overcome various kinds of malnutrition or undernutrition problems in toddlers, pregnant women and breastfeeding mothers. The purpose of this study was to determine the effect of giving Moringa Leaf Clear Vegetables to Breastfeeding Mothers aged 0-2 years in the Legung Health Center Work Area. Research Methods Experimental research using Quasi Experimental Design. Sampling technique in this study using Simple Random Sampling of 60 populations. The sample in this study were mothers who breastfed infants aged 0-2 years as many as 42 samples. 21 samples of the treatment group and 21 samples of the control group. Statistical test found that the value of sig (2-tailed) P = 0.000 0.05, it can be concluded that there is an effect of giving Moringa leaf clear vegetables on breast milk production in breastfeeding mothers aged 0-2 years in the working area of the legung health center. So it can be concluded that there is an effect of giving Moringa leaf clear vegetables on breast milk production in breastfeeding mothers aged 0-2 years in the working area of the Leung Health Center.